Pengabdian Berbasis Sportivitas: Kontribusi Dosen Sebagai Wasit Dan Hakim Pada Prapopnas Cabor Tinju - Irawan, Safri; Haryani, Meri; Lamusu, Zulkifli (Jambura Arena Pengabdian, 2024)
This community service program aims to support the implementation of Prapopnas in the boxing category held in Gorontalo by involving lecturers as referees and judges. The program was designed to address partner issues related to the lack of competent officials, which could undermine the quality and credibility of the competition. Through a continuous education approach and consultations, participating lecturers underwent intensive training to enhance their understanding of match regulations and decision-making. The outcomes indicate the successful execution of fair, sportsmanlike, and conflict-free matches. Success indicators include partner satisfaction levels, improved local committee competencies, and comprehensive activity documentation. Key supporting factors were the lecturers' competencies, effective coordination, and participants' enthusiasm. Challenges, such as limited facilities, were overcome through effective communication among stakeholders. This activity contributes to promoting the values of sportsmanship and professionalism in student-level sports achievements.